2023
DOI: 10.3389/fpls.2023.1125382
|View full text |Cite
|
Sign up to set email alerts
|

MYB pathways that regulate UV-B-induced anthocyanin biosynthesis in blueberry (Vaccinium corymbosum)

Abstract: Ultraviolet-B (UV-B) promotes anthocyanin accumulation and improves fruit quality in plants. To explore the underlying network of MYB transcription factors that regulates UV-B-induced anthocyanin biosynthesis in blueberry (Vaccinium corymbosum), we analyzed the response of MYB transcription factor genes to UV-B treatment. Transcriptome sequencing analysis revealed that VcMYBA2 and VcMYB114 expression were upregulated and were positively correlated with the expression of anthocyanin structural genes under UV-B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The groups IV and V contain one or two B-box domains without CCT domain. At same time, VcBBX21 , VcBBX24 , and VcBBX30-32 response to UV-B radiation, and UV-B radiation involve in color of flower and fruit [ 48 ]. In apple, MdBBX20, MdBBX22, MdBBX33 and MdBBX54 of group IV with two B-box domains without CCT domain regulate UV-B-induced anthocyanin biosynthesis and MdBBX37 of group V with one B-box domain without CCT domain also regulates anthocyanin biosynthesis [ 20 , 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The groups IV and V contain one or two B-box domains without CCT domain. At same time, VcBBX21 , VcBBX24 , and VcBBX30-32 response to UV-B radiation, and UV-B radiation involve in color of flower and fruit [ 48 ]. In apple, MdBBX20, MdBBX22, MdBBX33 and MdBBX54 of group IV with two B-box domains without CCT domain regulate UV-B-induced anthocyanin biosynthesis and MdBBX37 of group V with one B-box domain without CCT domain also regulates anthocyanin biosynthesis [ 20 , 22 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pear, PpBBX16, PpBBX18 and PpBBX21, with two B-box domains without CCT domain, regulate anthocyanin accumulation [ 59 , 60 ]. The previous study showed that VcBBX30 and VcBBX32 co-expressed with the possible anthocyanin biosynthesis gene VcMYBA2 and VcMYB114 under UV-B radiation [ 48 ]. Thus, VcBBX21 , VcBBX24 , and VcBBX30-32 , especially VcBBX30 and VcBBX32 , may regulate UV-B-induced anthocyanin biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the expression of MYBA1 and MYBA2 genes (subgroup 6) were upregulated under exogenous ABA treatment (Figure 5). In which, the MYBA2 gene expression was upregulated, was positively correlated with the expression of ASGs under UV-B radiation and played an important role in the UV-B-induced anthocyanin biosynthetic pathway [70]. MYBA1 has been reported as VcMYB437and the expression of VcMYB437 was higher in the skin of ripe blueberry fruit than in the pulp, implying the potential roles in anthocyanin biosynthesis [71].…”
Section: The Regulatory Network Of Aba-induced Blueberry Anthocyanin ...mentioning
confidence: 98%
“…As MYB12 and MYB111 have been proven to play a crucial role in the production of flavonol glycoside in response to UV-B radiation [41,42], we further explore the sequence and expression pattern of LcMYB12 and LcMYB111 identified by the above WGCNA analysis. Firstly, a phylogenetic tree was constructed for LcMYB111 and LcMYB12 with other MYB111s, which could be up-regulated by UV-B radiation, including AtMYB111, AtMYB12, HaMYB111 [43], CsMYB12 [44], VcMYB114 [45], PpMYB-FL [46] and VviMYBF1 [47]. Phylogenetic analysis revealed that LcMYB111 clustered together with AtMYB111, while LcMYB12 clustered together with AtMYB12 (Figure 7A), indicating that they are homologs of AtMYB111 and AtMYB12 in litchi.…”
Section: Key R2r3-myb Transcription Factors Up-regulated By Uv-b Radi...mentioning
confidence: 99%